Building Community Online: Moving toward Humanization Through Relationship-Focused Technology Use - Gilpin, Staci Ann; Yoon, Stephanie Rollag; Miller, Jana LoBello (Online Learning, 2023)
This qualitative study aims to improve accessibility and equity in digital spaces by identifying the prevalent mismatch between online course design, student culture, and its connection to instructional design for teacher preparation programs. Utilizing feminist theory, we explore the intersection between community, identity, and learning within relational-focused small group online discussions for students enrolled in two online teacher preparation courses. Data for this study includes observations of teacher candidates, artifacts of their meetings, and reflective responses. The results indicate that relational-focused small group online discussions provide opportunities to expand accessibility and equity through community and deep learning while impacting future teachers’ identities.